Statistical overstatement of average wages and its impact on pensions: The case of Hungary - Gábor Obláth; András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2024)
In Hungary, initial pensions are indexed to average net wages, reported by official earnings statistics (ES), which does not cover the economy as whole. However, there is alternative statistical source on labour income, the national accounts (NA), intended to cover the total economy. The latter indicate a markedly lower rate of growth in wages than the ES for the period between 2010 and 2020 (4.9 vs. 1.9 percent increase in real gross wages per year). Relying on feasibility tests, we show that the rapid increase reported by the ES cannot, while the milder growth shown by the NA can be reconciled with relevant macroeconomic developments, e.g., changes in productivity and household consumption. We, therefore, claim that the ES overstated the actual increase in wages at the national level during the 2010s, and make our own calculations regarding the path of net wages and implied (hypothetical) initial pensions. The main implications of this exercise are the following: (i) the actual increase in initial benefits (linked to net wages, as reported by the ES) was excessive; (ii) in our estimate, the ratio of average benefits to average net wages did not fall by the extent shown by official statistics (the former is linked to the increase in prices, rather than that of wages). Moreover, (iii) the accumulation of major tensions between cohorts retiring in subsequent years might have been reduced by relying on the more plausible wage statistics reported by the NA, and by taking into account the impact of the dramatically reduced social contribution rate (paid by employers) in calculating initial benefits.
Keywords: H55; 330; alternative measures of average wages; pensions; indexation of initial pensions; Hungary